Pengaruh Kampanye "Waste Down, Kindness Up" di Instagram Sociolla terhadap Perubahan Perilaku Masyarakat - Alifia Zahira Shofa Setyawan; Jovanka Maura Adhisty (Jurnal Nomosleca, 2022)
The accumulation of garbage that is increasing day by day is increasing Sociolla and Sukin's intention to collaborate and work with Waste4Change to jointly invite the community to preserve the environment, one of which is by recycling used packaging for beauty products. This intention was conveyed by Sociolla through the "Waste Down, Kindness Up" campaign on Instagram. This study aims to see whether the campaign carried out on Sociolla’s Instagram has an effect on changing people's behavior to reduce product waste. The method used in this study is quantitative by using a questionnaire as a data collection instrument which was distributed to 100 Instagram Sociolla followers randomly. The results showed that the influence of the campaign on changes in people's behavior was 22.1%.Keywords: Campaign, Recycle, Changes in Behavior.